2001
DOI: 10.1097/00005768-200112000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Peak power output, the lactate threshold, and time trial performance in cyclists

Abstract: The results of this study demonstrate that in subelite cyclists the relationship between maximum power output and the power output at the lactate threshold, obtained during an incremental exercise test, may change depending on the length of the TT that is completed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 26 publications
9
76
0
3
Order By: Relevance
“…Tradicionalmente, o LL tem sido identificado em diferentes tipos de exercícios, especialmente de características cíclicas 5 , e mais recentemente no exercício resistido (ER), com grande validade ecológica, por ser amplamente empregado na avaliação e prescrição do exercício no treinamento atlético e na reabilitação física 6 , visando benefícios cardiovasculares 7 , neuromusculares 8 e metabólicos 9 . No entanto, sua prescrição utiliza-se basicamente de métodos tradicionais para avaliação e acompanhamento da evolução no treinamento físico.…”
Section: Resumen Introducción: El Umbral Anaeróbico Se Identifica Comunclassified
“…Tradicionalmente, o LL tem sido identificado em diferentes tipos de exercícios, especialmente de características cíclicas 5 , e mais recentemente no exercício resistido (ER), com grande validade ecológica, por ser amplamente empregado na avaliação e prescrição do exercício no treinamento atlético e na reabilitação física 6 , visando benefícios cardiovasculares 7 , neuromusculares 8 e metabólicos 9 . No entanto, sua prescrição utiliza-se basicamente de métodos tradicionais para avaliação e acompanhamento da evolução no treinamento físico.…”
Section: Resumen Introducción: El Umbral Anaeróbico Se Identifica Comunclassified
“…The determination of physiological variables, such as the anaerobic threshold and maximal oxygen uptake, will help in realization of the major requirement for coaches and athletes: to define the endurance performances of athletes (Bentley et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an early study by Farrell et al [59] reported stronger relationships (r ≥ 0.91; all p < 0.05) between the treadmill velocity corresponding to the onset of plasma lactate accumulation (defined as the velocity just prior to the exponential increase in plasma [La -]) and running performances over 3.2 -42.2 km in experienced male distance runners, than between V O2max and performance (r = 0.83-0.91; all p < 0.05; n = 18) [59] . Subsequent investigations have provided support for these findings and although LT2 determination methods are now quite diverse, research has consistently shown that LT2 parameters are stronger correlates of endurance performance than V O2max is [5,10,17,74] . 36 Bishop et al [10,17] reported in two separate studies that 1 h cycle time trial performance correlated more strongly with LT2 measured via six different methods (r = 0.61-0.84; all p < 0.01 [10] and r = 0.71 -0.89; all p < 0.05 [17] ) than with V O2peak…”
Section: Fractional Utilisation Of V O 2 Maxmentioning
confidence: 93%
“…Nevertheless, V O2max may not be the most sensitive measure to detect performance changes throughout an athlete's season and subsequently, may not require frequent testing. In a highlytrained population it appears that changes in performance may be equally or more strongly correlated with other variables such as running economy [73] , the velocity [74,75] and power output [5,10] at V O2max and the fractional utilisation of V O2max (as determined through the assessment of lactate or ventilatory data) [5,6] . These findings will be discussed in subsequent sections of this review.…”
Section: O2max and Exercise Training In Trained Athletesmentioning
confidence: 99%
See 1 more Smart Citation